Social Science Learning in Primary School Responding to The Challenges Of 21st Century Education - Esty Setyo Utaminingsih (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2023)
Social science learning at the elementary school level plays a vital role in preparing future generations according to the demands of the 21st century. This study aims to examine more about social science learning in primary schools responding to the challenges of 21st-century education. The method in this study uses the method of literature review, which collects articles relevant, and then reduces the most appropriate and relevant articles to strengthen existing theories or findings. The results showed that social studies learning plays an important role in responding to the challenges of the 21st century, such as guiding students to have the ability to think critically, care about global issues, have digital literacy skills, and socio-cultural skills. This implies that more attention is needed to social studies learning in elementary schools, and teachers need to innovate learning so that student social studies learning motivation increases so that students are equipped to face the challenges of the 21st century.Keywords: Social Science, Primary School, Elementary School, 21st-century